Time course of the effects of lisdexamfetamine dimesylate in two phase 3, randomized, double‐blind, placebo‐controlled trials in adults with binge‐eating disorder. Issue 8 (8th May 2017) - McElroy, Susan L.; Hudson, James I.; Gasior, Maria; Herman, Barry K.; Radewonuk, Jana; Wilfley, Denise; Busner, Joan
Abstract: Objective: This study examined the time course of efficacy‐related endpoints for lisdexamfetamine dimesylate (LDX) versus placebo in adults with protocol‐defined moderate to severe binge‐eating disorder (BED). Methods: In two 12‐week, double‐blind, placebo‐controlled studies, adults meeting DSM‐IV‐TR BED criteria were randomized 1:1 to receive placebo or dose‐optimized LDX (50 or 70 mg). Analyses across visits used mixed‐effects models for repeated measures (binge eating days/week, binge eating episodes/week, Yale‐Brown Obsessive Compulsive Scale modified for Binge Eating [Y‐BOCS‐BE] scores, percentage body weight change) and chi‐square tests (Clinical Global Impressions—Improvement [CGI‐I; from the perspective of BED symptoms] scale dichotomized as improved or not improved). These analyses were not part of the prespecified testing strategy, so reported p values are nominal (unadjusted and descriptive only). Results: Least squares mean treatment differences for change from baseline in both studies favored LDX over placebo (all nominal p values <  .001) starting at Week 1 for binge eating days/week, binge‐eating episodes/week, and percentage weight change and at the first posttreatment assessment (Week 4) for Y‐BOCS‐BE total and domain scores. On the CGI‐I, more participants on LDX than placebo were categorized as improved starting at Week 1 in both studies (both nominal p values <  .001). Across these efficacy‐related endpoints, the superiority of LDX over placebo was maintained at each posttreatment assessment in both studies (all nominal p values <  .001). Discussion: In adults with BED, LDX treatment appeared to be associated with improvement on efficacy measures as early as 1 week, which was maintained throughout the 12‐week studies.